Planetary Ethics: Russell Train and Richard Nixon at the Creation - Annas, George J. (The Hastings Center report, 2020)
This piece offers a retrospective review of a plenary speech at the 1969 Annual Meeting of the American Public Health Association by the leading environmentalist of the Nixon administration, attorney and judge Russell Train. Train's talk, titled “Prescription for a Planet,” can be seen as an early argument for uniting environmental health and public health as the two main determinants of both individual and population health and for the inclusion of these fields in the then-new field of “bioethics.”